2021
DOI: 10.1177/0271678x211056393
|View full text |Cite
|
Sign up to set email alerts
|

Lower cerebral oxygen utilization is associated with Alzheimer’s disease-related neurodegeneration and poorer cognitive performance among apolipoprotein E ε4 carriers

Abstract: Oxygen extraction fraction (OEF) and cerebral metabolic rate of oxygen (CMRO2) are markers of cerebral oxygen homeostasis and metabolism that may offer insights into abnormal changes in brain aging. The present study cross-sectionally related OEF and CMRO2 to cognitive performance and structural neuroimaging variables among older adults (n = 246, 74 ± 7 years, 37% female) and tested whether apolipoprotein E ( APOE)-ε4 status modified these associations. Main effects of OEF and CMRO2 were null (p-values >0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…135 Studies have shown that the APOE ε4 allele imposes a great risk for developing dementia, since it regulates several key genes which are involved in function of brain. 136 A cohort study conducted by Robb et al 137 on 246 APOE ε4 carriers and non-carriers aimed to test whether APOE ε4 status could impact cerebral oxygen homeostasis and cognitive performance. The authors found that APOE4 carriers are often manifested with lower cerebral oxygen metabolism, interacting with the pathogenesis of AD and related neurodegeneration.…”
Section: Mtor and Vascular Dysfunctionmentioning
confidence: 99%
“…135 Studies have shown that the APOE ε4 allele imposes a great risk for developing dementia, since it regulates several key genes which are involved in function of brain. 136 A cohort study conducted by Robb et al 137 on 246 APOE ε4 carriers and non-carriers aimed to test whether APOE ε4 status could impact cerebral oxygen homeostasis and cognitive performance. The authors found that APOE4 carriers are often manifested with lower cerebral oxygen metabolism, interacting with the pathogenesis of AD and related neurodegeneration.…”
Section: Mtor and Vascular Dysfunctionmentioning
confidence: 99%
“…The brain has a high metabolic demand for oxygen compared to other organs since the human brain comprises just 2% of the total body mass but consumes 20% of available oxygen for normal function (Rolfe and Brown, 1997), so regulation of cerebral blood flow (CBF) and oxygen delivery is critically important. Oxygen extraction fraction (OEF) is a key hemodynamic parameter to measure the brain's energy metabolism and is altered in aging and disease processes, including cerebrovascular disorders (Watchmaker et al, 2018;Fan et al, 2022;Liu et al, 2023), neurodegeneration (Jiang et al, 2020;Robb et al, 2022), and neuroinflammation (Cleland et al, 2021). In some pathological mechanisms, OEF is reduced concurrently with hypoperfusion due to decreased neural activity and lower oxygen metabolic demand (Ishii et al, 1996;Brown and Thore, 2011); while in other distinct mechanisms, OEF is elevated in areas of hypoperfusion, indicating physiological compensation in tissue that is at ischemic risk (Gupta et al, 2014;Fan et al, 2020;Lin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%